2014
DOI: 10.1021/jo500664e
|View full text |Cite
|
Sign up to set email alerts
|

Computational Rationalization for the Observed Ground-State Multiplicities of Fluorinated Acylnitrenes

Abstract: Computational methods are used to investigate the mechanism by which fluorination of acetylnitrene reduces the stabilization of the singlet configuration. ΔEST is made more positive (favoring the triplet state) by 1.9, 1.3, and 0.7 kcal/mol by the addition of the first, second, and third fluorine, respectively, at the CR-CC(2,3)/6-311(3df,2p)//B3LYP/6-31G(d,p) level of theory. Smaller effects observed with substitution of β-fluorines in propanoylnitrene derivatives and examination of molecular geometries and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…We then conducted several control experiments to try to understand the reaction mechanism (Scheme 4). Generation of an N-acylnitrene species [17] could not be involved under the present reaction conditions,asithas been reported that such species immediately insert into MeCN to afford oxadiazole 13;t he characteristic À66.8 ppm 19 FNMR peak of this compound was not observed at all (Scheme 4a). Theaddition of ar adical scavenger,s uch as (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) or butylated hydroxytoluene (BHT), significantly decreased the chemical yield of 8a when silyl enol ether 7aand iodinane 3c reacted under photoirradiation conditions,s uggesting that ar adical intermediate is involved in the reaction (Scheme 4b).…”
Section: Angewandte Chemiementioning
confidence: 53%
See 1 more Smart Citation
“…We then conducted several control experiments to try to understand the reaction mechanism (Scheme 4). Generation of an N-acylnitrene species [17] could not be involved under the present reaction conditions,asithas been reported that such species immediately insert into MeCN to afford oxadiazole 13;t he characteristic À66.8 ppm 19 FNMR peak of this compound was not observed at all (Scheme 4a). Theaddition of ar adical scavenger,s uch as (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) or butylated hydroxytoluene (BHT), significantly decreased the chemical yield of 8a when silyl enol ether 7aand iodinane 3c reacted under photoirradiation conditions,s uggesting that ar adical intermediate is involved in the reaction (Scheme 4b).…”
Section: Angewandte Chemiementioning
confidence: 53%
“…[16] We envisioned that ortho substituents would stabilize the N-trifluoroacetyliminoiodinane,a sw ell as improve its solubility,t oe nable its isolation (Scheme 1b). Furthermore,s uch coordinating groups would also stabilize the photoexcited state of the iminoiodinane,p reventing generation of free nitrenes, [17] which can afford undesired products through non-selective reactions.Instead, the desired amidyl radical species [14,18] would be generated to achieve additive-free amination.…”
mentioning
confidence: 99%
“…16 Quite recently, the ground-state multiplicities of fluorinated acylnitrenes, including FC(O)N, were computationally rationalized. 22 For fluoroalkylcarbonyl azides (e.g., CF 3 C(O)N), the electron-withdrawing effect of the fluorine was found to reduce the relative stability of the singlet configuration. However, because of direct conjugation between the fluorine and carbonyl, FC(O)N is electronically more closely related to the ROC(O)N nitrenes and a larger ΔE ST is predicted.…”
mentioning
confidence: 99%
“…As one of the simplest carbonyl nitrenes, trifluoroacetyl nitrene, CF 3 C(O)N, has attracted both theoretical and experimental interest. Time‐resolved infrared spectroscopy study on the flash photolysis (266 nm) of N ‐trifluoroacetyl dibenzothiophene sulfilimine in CH 2 Cl 2 and CH 3 CN failed to obtain conclusive evidence for the formation CF 3 C(O)N, one transient band at 1660 cm −1 was tentatively assigned to the nitrene in the singlet state despite the large discrepancy with the calculation, whereas, product analysis clearly indicates triplet reactivity …”
Section: Methodsmentioning
confidence: 60%